QUESTION AND ANSWER RELATIONSHIP AND READING COMPREHENSION DEVELOPMENT AMONG THE SOPHOMORE NURSING STUDENTS - Situmeang, Anas; Kristianto, Eko; Panjaitan, Nelson B. (Journal of Language Pedagogy, 2011)
The research was administrated to answer the question âis there any significance improvement after they used the Question and Answer Relationship reading strategy?â The data were collected through pre-test and post-test, administered to 29 students and the data was analyzed by using T-test. From the computation of the pre-test and post-test, the result showed that the participantsâ comprehension achievement was improved through QAR strategy and the score gained by the participants showed that there was a significant effect of QAR strategy. It is strong enough to improve the studentsâ reading comprehension. The achievements showed that mean difference between pre-test and post-test is 8.7. The tcounted = 6.37 > ttable = with significance level in 0.00.Â  Standard error mean of the pre-test is 1.15446 and post-test is 0.77600. The researcher hopes that the finding of present study could give some contribution to the improvement on the teaching reading especially for the faculty of Education at Universitas Advent Indonesia.